Owls - Mikkola, Heimo (IntechOpen, 2020)
Owls are soft-plumaged, short-tailed, big-headed birds that have the most frontally situated eyes of all birds and they can blink the upper eyelids. This, together with a broad facial disc, gives owls all the right characteristics to make them attractive in our eyes. At the same time, some people fear their presence and even their calls, and there are more myths and beliefs about owls than there are about any other bird.Bats are often similarly feared as owls, partly because both of them inhabit the night; a place that is unknown and alien to us. Owls and bats symbolise all that is mysterious about the night and their complete mastery of the darkness only highlights our own deficiencies. In this book, we will get to know the relationships between bats and owls. This book describes the biological control of rats by owls in Malaysia, the prey-predator interactions in a tropical forest in Mexico, and provides an overview of the breeding biology of owls. From numerous owl belief and myth studies, described in this book are those of the lesser known Central Asian countries where owls are often worshipped for their supernatural powers.